Teaching Strategies to Improve Students' Critical Thinking Skills Through the Integration of Islamic Educational Philosophy Values - Usiono Usiono; Junaidi Arsyad; Retno Sayekti; Eka Yusnaldi; Budiman Budiman (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to analyze the integrated Islamic educational philosophy value learning strategy to improve students' critical thinking skills at Indonesian Islamic Universities, Islamic religious education study program. Islamic philosophical values ​​include adab (civility), morals, and akhlak (ethics). A qualitative approach was used with 12 informants, consisting of lecturers and heads of study programs. The informants were selected purposively. Data were collected through in-depth interviews and analyzed inductively using thematic analysis. The results show that lecturers' empirical experiences in teaching practice confirm the effectiveness of case study-based strategies, reflective discussions, academic debates, and problem-based learning in fostering critical thinking in students. The success of these strategies is reflected in students' ability to construct logical arguments, conduct in-depth analyses, and integrate morals, adab (civility), and akhlak (ethics) into learning. The main obstacles were variations in student participation and time constraints, but these can be minimized through lecturers' creativity in designing learning. This research contributes to the development of applicable learning strategies based on morals, adab, and akhlak through the application of participatory methods and ongoing institutional support. The integration of Islamic educational philosophy values ​​strengthens students' moral and spiritual dimensions.